Edukasi Penguatan Ketahanan Keluarga Sebagai Landasan Kesejahteraan - Fahmy Akbar Idries; Novi Diah Wulandari; Febriani Wahyusari N; Agustina Agustina; Miqod Adi Guna (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
This workshop is focused on the education and empowerment of families to enhance their resilience as the foundation for well-being. Participants gain insights into the core concept of family resilience and acquire practical strategies to strengthen their families against various social and non-social challenges. The workshop includes interactive elements, including presentations, discussions, and practical activities, allowing participants to share experiences and learn collaboratively. The program emphasizes the importance of education in the family context and aims to equip participants with knowledge about family resilience. In conclusion, this workshop not only enriches participants' knowledge but also provides a platform for the development of practical skills and broader networking opportunities. The expected outcomes of this activity are to have a sustained positive impact on family resilience, contributing to the overall well-being of the community. The collaborative efforts of participants, partners, and stakeholders mark a meaningful beginning in building family resilience for collective prosperity.